2020
DOI: 10.1016/j.waojou.2020.100445
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunotherapy for peanut allergy: The con argument

Abstract: Background: In some countries of the world, peanut allergy represents an important source of anaphylactic reactions. Traditionally treated with the avoidance of responsible allergens, this condition can also be targeted by oral peanut immunotherapy. Methods: In this study, we review the beneficial and side effects of currently available forms of peanut oral immunotherapy (POIT). We report the discussions resulting from the publication of a meta-analysis that brought to light the downsides of oral immunotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…51,56 In line with previous clinical experience, OMA showed no major safety concerns in patients with IgE-mediated FA. In OIT protocols, safety is a major concern 64,65 ; however, reductions in adverse reactions were noted in subjects receiving OMA during OIT dose escalation, dose-related reactions necessitating treatment, and doses needed to achieve maintenance. 16 Studies have indicated that OMA can decrease episodes of anaphylaxis in patients with recurrent and/or unprovoked anaphylactic reactions, 47 reiterating a potential benefit, especially in patients at a high risk of FA-related severe anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…51,56 In line with previous clinical experience, OMA showed no major safety concerns in patients with IgE-mediated FA. In OIT protocols, safety is a major concern 64,65 ; however, reductions in adverse reactions were noted in subjects receiving OMA during OIT dose escalation, dose-related reactions necessitating treatment, and doses needed to achieve maintenance. 16 Studies have indicated that OMA can decrease episodes of anaphylaxis in patients with recurrent and/or unprovoked anaphylactic reactions, 47 reiterating a potential benefit, especially in patients at a high risk of FA-related severe anaphylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…In its phase 1, an Omalizumab/placebo comparison will assess among patients allergic to peanuts and other foods the ability to reach a full‐serving size threshold at DBPCFC after 16–20 weeks of treatment. A further 24‐weeks extension will evaluate if a prolonged Omalizumab treatment increases the probability of patients to introduce foods 102 …”
Section: Monoclonal Antibodies Showing Promise In Clinical Trials For Ige‐mediated Food Allergymentioning
confidence: 99%
“…Specifically, peanut oral immunotherapy (pOIT) is able to induce tolerance/desensitization. 3 While the pathogenesis of food allergy is relatively well-studied, 4 mechanisms of OIT-induced tolerance are not well understood. Omalizumab (anti-IgE), which is used as treatment for severe allergic asthma and other IgE-driven allergies, can also facilitate OIT initiation 5 ; however, little is known about the involved mechanisms, including possible changes at the transcriptional level.…”
Section: E T T E R T O T H E E D I T O R Transcriptome Changes During...mentioning
confidence: 99%
“…Simon Kebede Merid 1 David Brodin 2 Josef Brandström 3,4 Fredrik Fagerström-Billai 2 Marieke van der Heiden 5 Jon R. Konradsen 4 Michael Kabesch 6 Cornelis M. van Drunen 7 Korneliusz Golebski 8,9 Anke H. Maitland-van der Zee 9 Uroš Potočnik 10,11 Susanne J. H. Vijverberg 9 Anna Nopp 1,12 Caroline Nilsson 1,12 Erik Melén…”
Section: Ack N Owled G Em Entsunclassified